Synergistic effects between κ-carrageenan and locust bean gum on physicochemical properties of edible films made thereof - Martins, Joana (2012)
The development of mixed systems, formed by locustbeangum (LBG), and κ-carrageenan (κ-car) can offer new interesting applications such as the development of ediblefilms with particular properties. κ-car/LBG blend films with different ratios were developed, and their effects on films’ physical properties were assessed. Thermogravimetric analysis (TGA), X-ray diffraction (XRD) patterns, dynamic mechanical analysis (DMA) and Fourier-transform infrared (FTIR) spectroscopy techniques were used to highlight the interactions between the two polysaccharides. The addition of κ-car to LBG improved the barrier properties of the films leading to a decrease of water vapor permeability (WVP). Improved values of elongation-at-break (EB) were registered when the ratio of κ-car/LBG was 80/20 or 40/60 (% w/w). Moreover, the κ-car/LBG blend films enhance the tensile strength (TS) compared to κ-car and LBG films. FTIR results suggested that hydrogen bonds interactions between κ-car and LBG have a great influence in films’ properties e.g. moisture content, WVP. Therefore, different κ-car/LBG ratios can be used to tailor ediblefilms with enhanced barrier and mechanical properties.